2011
DOI: 10.1007/s13157-011-0239-7
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Morphological Problems in the Yangtze Estuary and the Western Scheldt

Abstract: This paper compares the Yangtze Estuary in China and the Western Scheldt Estuary in The Netherlands by their morphodynamic and ecological systems, their engineering works and estuarine management issues, and the major challenges in studying them. Physically speaking, the two estuaries are very different. The Yangtze Estuary is much larger and much more influenced by the upstream river than the Western Scheldt. Yet, they also have a number of morphological and ecological features in common. Both estuaries have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 32 publications
0
66
0
Order By: Relevance
“…The estuary experiences a semidiurnal tide, with a mean tidal range of 3.8m at the mouth, and 5m at the Dutch-Belgian border (Eleveld et al, 2014). The estuary is turbid, well-mixed and river discharge is low, ca 100 m 3 s -1 (De Vriend et al, 2011;Eleveld et al, 2014).…”
Section: Study Areamentioning
confidence: 99%
“…The estuary experiences a semidiurnal tide, with a mean tidal range of 3.8m at the mouth, and 5m at the Dutch-Belgian border (Eleveld et al, 2014). The estuary is turbid, well-mixed and river discharge is low, ca 100 m 3 s -1 (De Vriend et al, 2011;Eleveld et al, 2014).…”
Section: Study Areamentioning
confidence: 99%
“…The Scheldt estuary experiences a number of human-induced processes that can increase sediment deposition on tidal flats, among which dredging and the local deposition of dredged sediments at the edges of tidal flats are some of the most important examples (De Vriend et al, 2011;van der Wal et al, 2011). The Paulina mudflat harbours a functionally rich benthic macrofaunal community that is numerically dominated by polychaetes (Van Colen et al, 2008.…”
Section: Sample Collection and Experimental Set-upmentioning
confidence: 99%
“…Our study was performed on a mudflat in the estuary of the river Scheldt (Belgium, the Netherlands), which is characterized by its meso-to macrotidal regime and well-mixed water column. Sediment input from the river basin is relatively low and sand extraction and sea level rise lead to a net export of sediment from the estuary (De Vriend et al, 2011). Sediment accretion on the estuary's tidal flats can amount to about 2 cm yr −1 (Weerman et al, 2011;Widdows et al, 2004), which suggests that natural sedimentation on the intertidal mudflats is unlikely to exceed even a few millimetres per tidal cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bouma et al, 2005). For example in the Western Scheldt, the shipping fairway is now maintained at a depth of 14.5m below Lowest Astronomical Tide (de Vriend et al, 2011;Depreiter et al, 2012 In contrast, low-dynamic intertidal areas are valuable ecological habitat, for example for the Western Scheldt there is an obligation to maintain a certain amount of intertidal area (Depreiter et al, 2012). Previously, Townend (2008) showed that 15 basin hypsometry can be a tool to design breaches in managed re-alignment sites and can provide an indication of habitat composition.…”
Section: Implications For Management Of Estuariesmentioning
confidence: 99%